MATCHING OF UNIVERSITY FACULTY’S POSITIONS AND PROMOTION PRO-CEDURES IN THE LEADING COUNTRIES OF THE WORLD - Tatiana E. Isaeva (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
Due to the creation of the unified European educational area and an increase of the teachers’ mobility the problem of the professional activity of the university professors has become one of the most acute for Russian and foreign educational institutions. Matching of academic titles and positions of the teachers who work in the universities of Russia, Europe, Asia and the USA has always been a complicated task due to the availability of various requirements that were claimed to them, basing on the status of the university and its type as well as differences in the approaches to the teacher’s activity estimation. After making a comparative analysis we succeeded in defining of several models of academic titles and university teachers’ positions that appeared under the influence of historical traditions, political factors as well as community’s perception of the prestigiousness of the higher education in this or that country.